2002
DOI: 10.1021/ja012243c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Atom Abstraction Reactions of Charged Polyaromatic σ-Radicals Related to the Active Intermediates of the Enediyne Antitumor Drugs

Abstract: Polar effects are demonstrated to play an important role in controlling the reactivity of polyaromatic sigma-radicals that are structurally related to the active intermediates of the enediyne anticancer type antibiotics. This was accomplished by measuring the rate constants of hydrogen atom abstraction for novel, charged dehydroquinolines, dehydroisoquinolines, dehydrobenzenes, and dehydronaphthalenes in the gas phase by using Fourier-transform ion cyclotron resonance mass spectrometry. The reactivity trends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…These findings are in agreement with previous gas-phase studies that indicated enhanced reactivity when the EA of the radical site increases. 19,21,33 For the 2-dehydropyridinium cation, the percentage yields of hydrogen atom abstraction were found to be unaffected by pH. This is because of formation of a second reaction intermediate, the 2-pyridyl cation, which complicates the experiment in solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with previous gas-phase studies that indicated enhanced reactivity when the EA of the radical site increases. 19,21,33 For the 2-dehydropyridinium cation, the percentage yields of hydrogen atom abstraction were found to be unaffected by pH. This is because of formation of a second reaction intermediate, the 2-pyridyl cation, which complicates the experiment in solution.…”
Section: Resultsmentioning
confidence: 99%
“…These radicals were selected since their reactivity has been already examined in the gas phase. 19,21,32,33 …”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atom abstraction reactions were the sole reactions observed when distonic ions 17 - 23 were allowed to react with tetrahydrofuran and 2-methyltetrahydrofuran, while cyano radical and hydrogen cyanide abstraction reactions were observed with tert -butyl isocyanide. 148 The trends observed for the reactivities of these radicals were found not to arise from differences in reaction enthalpy, size of the radical, or the position of the radical site in the aromatic ring system. Analogous to the results discussed above, the reactivity of these radicals directly correlates with the calculated vertical electron affinities (EA v s) of their radical sites.…”
Section: Properties and Reactivitymentioning
confidence: 88%
“…67,68,148 In general, the distonic ions were generated in a dual-cell FT-ICR by subjecting appropriate protonated precursors to sustained off-resonance collision-activated dissociation (SORI-CAD) to cleave either a weak C-I or C-NO 2 bond. Hydrogen atom abstraction reactions were the sole reactions observed when distonic ions 17 - 23 were allowed to react with tetrahydrofuran and 2-methyltetrahydrofuran, while cyano radical and hydrogen cyanide abstraction reactions were observed with tert -butyl isocyanide.…”
Section: Properties and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation